Wernicke's Encephalopathy: Atypical Manifestation at MR Imaging - Bae, Sang-Jin (AJNR Am J Neuroradiol, 2001)
Summary: We report a case of atypical manifestation of hyperintense lesions in a 64-year-old female patient with Wernicke's encephalopathy. Fluid-attenuated inversion recovery and T2-weighted images demonstrated symmetrical distribution of hyperintense lesions in cerebellar dentate nuclei, tegmentum of the lower pons, red nuclei, and tectum of the midbrain, and T1-weighted sagittal images showed atrophy of the mamillary bodies. The hyperintense lesions were completely resolved on follow-up MR images.